The Relationship Between Soft Skills and Job Readiness of Industrial Mechanical Engineering Students at SMK Pasundan 2, Serang City - dika, Ardhika Achmad Gustama; Putra, Ananda Yhuto Wibisono; Abizar, Haris (The Future of Education Journal, 2025)
This study aims to identify the relationship between soft skills and job readiness among 12th-grade students in the Industrial Mechanical Engineering program at SMK Pasundan 2, Serang City. The research method used is a correlational study with a quantitative approach. The research was conducted at SMK Pasundan 2, Serang City, involving all 30 students from the 12th-grade Industrial Mechanical Engineering program as respondents, selected using a saturated sampling technique. Data collection was carried out through the distribution of questionnaires. The data analysis techniques used include validity testing, reliability testing, normality testing, and non-parametric hypothesis testing. The results of the analysis show that the Spearman's rho correlation coefficient is 0.648 with a significance of 0.000. Since the significance value is less than 0.05, it can be concluded that there is a significant relationship between the soft skills variable (X) and job readiness (Y).